Brain abscess in hepatopulmonary syndrome associated with biliary atresia. Issue 6 (10th September 2015) - Morita, Keiichi; Fukuzawa, Hiroaki; Maeda, Kosaku
Abstract: The first‐choice therapy for biliary atresia (BA) is Kasai hepatoportoenterostomy, which has been shown to greatly improve outcome. Various long‐term complications, however, such as portal hypertension and hepatopulmonary syndrome (HPS), can occur in patients with native liver. A rare case of brain abscess in an 11‐year‐old girl with HPS associated with BA is reported. The patient underwent hepatoportoenterostomy for BA at 53 days of age, with resolution of hyperbilirubinemia. At 10 years of age, she was diagnosed with severe HPS with right‐to‐left shunting, and preparations for liver transplantation proceeded. Three months after the diagnosis, she had a right parietal brain abscess. Given that the brain abscess enlarged in size, surgical drainage of the brain abscess was performed. The postoperative course was uneventful, but a slight left hemiplegia remained at discharge. The presumed mechanism of abscess formation in HPS may be right‐to‐left bacterial transit through intrapulmonary vascular dilatations and/or arteriovenous fistulae.